The Fabricated Hadith: A Review On Its Implication To Society - Abur Hamdi Usman; Ahamad Ahmadi Sakat; Fadlan Mohd Othman; Wan Nasyrudin Wan Abdullah; Mohd Fauzi Mohd Amin; Muhamad Rozaimi Ramle (PONTE Journal, Vallecchi Editore, 2024)
Non-Indexed Publication